The Whitehorse copper belt, Yukon Territory [electronic resource] - McConnell, R. G. (Richard George), 1857-1942.; Geological Survey of Canada. (Ottawa : C.M. Parmalee, 1909)
Tables. At head of title: Canada. Department of Mines. Geological Survey Branch . "Selected list of reports and maps . of special economic interest published by the Geological Survey Branch": 6 p. at end. "No. 1050." Includes index. Electronic reproduction. Mode of access: Internet. 44